Recurrent de-novo gain-of-function mutation in SPTLC2 confirms dysregulated sphingolipid production to cause juvenile amyotrophic lateral sclerosis - Dohrn, Maike F; Beijer, Danique; Lone, Museer A; Bayraktar, Elif; Oflazer, Piraye; Orbach, Rotem; Donkervoort, Sandra; Foley, A Reghan; Rose, Aubrey; Lyons, Michael; Louie, Raymond J; Gable, Kenneth; et al. (Journal of neurology, neurosurgery and psychiatry, 2024)
BackgroundAmyotrophic lateral sclerosis (ALS) leads to paralysis and death by progressive degeneration of motor neurons. Recently, specific gain-of-function mutations in SPTLC1 were identified in patients with juvenile form of ALS. SPTLC2 encodes the second catalytic subunit of the serine-palmitoyltransferase (SPT) complex.MethodsWe used the GENESIS platform to screen 700 ALS whole-genome and whole-exome data sets for variants in SPTLC2. The de-novo status was confirmed by Sanger sequencing. Sphingolipidomics was performed using liquid chromatography and high-resolution mass spectrometry.ResultsTwo unrelated patients presented with early-onset progressive proximal and distal muscle weakness, oral fasciculations, and pyramidal signs. Both patients carried the novel de-novo SPTLC2 mutation, c.203T>G, p.Met68Arg. This variant lies within a single short transmembrane domain of SPTLC2, suggesting that the mutation renders the SPT complex irresponsive to regulation through ORMDL3. Confirming this hypothesis, ceramide and complex sphingolipid levels were significantly increased in patient plasma. Accordingly, excessive sphingolipid production was shown in mutant-expressing human embryonic kindney (HEK) cells.ConclusionsSpecific gain-of-function mutations in both core subunits affect the homoeostatic control of SPT. SPTLC2 represents a new Mendelian ALS gene, highlighting a key role of dysregulated sphingolipid synthesis in the pathogenesis of juvenile ALS. Given the direct interaction of SPTLC1 and SPTLC2, this knowledge might open new therapeutic avenues for motor neuron diseases.